EXPERIMENTAL AND NUMERICAL INVESTIGATION OF HYBRID NANOFLUID WITH CORROBORATIVE CHARACTERISTICS FOR SOLAR COLLECTOR APPLICATIONS - HUSSEIN, OMAR ASSI (2021)
Adding metallic particles into thermal fluid systems has been widely considered as a promising approach to enhance heat transfer. However, the applications of the particlefluid mixtures are restricted due to the poor stability of those suspensions containing micro-sized particles. This study investigates the effect of using newly developed hybrid nanofluids as working fluid in flat plate solar collector (FPSC) to replace the conventional water-based fluid. The nanofluids assessed in this study are a combination of covalently functionalized-multi-walled carbon nanotubes (CF-MWCNTs) and covalently functionalized-graphene nanoplatelets (CF-GNPs) with hexagonal boron nitride (h-BN) in distilled water (DW) as base fluid. These nano additives are believed to enhance the conductivity of the fluid heat transfer and boost its thermal efficiency.